Antibiotic-induced DNA damage results in a controlled loss of pH homeostasis and genome instability - Booth, James Alexander; Špírek, Mário; Lobie, Tekle Airgecho; Skarstad, Kirsten; Krejci, Lumir; Bjørås, Magnar (Scientific reports, 2020)
Extracellular pH has been assumed to play little if any role in how bacteria respond to antibiotics and antibiotic resistance development. Here, we show that the intracellular pH of Escherichia coli equilibrates to the environmental pH following treatment with the DNA damaging antibiotic nalidixic acid. We demonstrate that this allows the environmental pH to influence the transcription of various DNA damage response genes and physiological processes such as filamentation. Using purified RecA and a known pH-sensitive mutant variant RecA K250R we show how pH can affect the biochemical activity of a protein central to control of the bacterial DNA damage response system. Finally, two different mutagenesis assays indicate that environmental pH affects antibiotic resistance development. Specifically, at environmental pH's greater than six we find that mutagenesis plays a significant role in producing antibiotic resistant mutants. At pH's less than or equal to 6 the genome appears more stable but extensive filamentation is observed, a phenomenon that has previously been linked to increased survival in the presence of macrophages.
Keywords: kyselina nalidixová; DNA Damage; průtoková cytometrie; ultrafialové záření; Anti-Bacterial Agents; nestabilita genomu; Nalidixic Acid; Microbial Viability; koncentrace vodíkových iontů; poškození DNA; rifampin; mikrobiální viabilita; Electrophoretic Mobility Shift Assay; Flow Cytometry; propidium; retardační test; Escherichia coli; Hydrogen-Ion Concentration; Rifampin; Genomic Instability; antibakteriální látky; Propidium; Ultraviolet Rays